An Upstream AG Determines Whether a Downstream AG Is Selected during Catalytic Step II of Splicing - Chua, Katrin (American Society for Microbiology, 2001)
Specific mechanisms must exist to ensure fidelity in selecting the AG dinucleotide that functions as the 3′ splice site during the second transesterification step of splicing. Here we show that the optimal location for this AG is within a narrow distance (19 to 23 nucleotides [nt]) downstream from the branch point sequence (BPS). Contrary to previous expectations, AGs located less than 23 nt from the BPS are always recognized, even when a second AG located more optimally downstream is used in the transesterification reaction. Indeed, the AG closest to the BPS actually dictates the precise location of the AG that engages in the reaction. This mechanism, in which the AG is identified by a general localization step followed by a precise localization step, may be used to achieve fidelity while allowing flexibility in the location of 3′ splice sites.